A Comprehensive Review Article on Severe Acute Respiratory Syndrome and Role of Antioxidants in its Prevention and Treatment - Pakeeza Abid; Anum Abbas; Seham Khan; Amna Inayat; Fahad Ahmed Kharal; Tariq Hussain; Tabish Ali Zeb (Khalij-Libya Journal of Dental and Medical Research, 2023)
The emergence of novel coronaviruses, including the severe acute respiratory syndrome and the more recent COVID-19 pandemic caused by SARS-CoV-2, has captured global attention due to their dangerous nature and potential for international harm. This comprehensive review delves into the historical evolution, virology, and clinical intricacies of these viruses. Beginning with the origins of SARS and its subsequent transmission, the article navigates through the epidemiology, pathogenesis, and clinical features, unraveling the complex interplay between these factors. Pivotal rigging role of antioxidants, including vitamins A, C, D, and pivotal minerals such as zinc, copper, selenium, and magnesium, is meticulously examined in relation to their potential to bolster immune responses and counteract oxidative stress. This review highlights the crucial significance of these antioxidants in both the prevention and treatment of viral infections. From the intricate virological structure to the transmission dynamics and the clinical manifestations that span from mild to severe, this paper meticulously unpacks the multifaceted nature of coronaviruses. Emphasizing the importance of swift intervention and preventive strategies, the article also explores antiviral therapies, convalescent plasma treatment, and vaccination efforts as essential tools in managing and preventing the spread of these viruses. The review underscores the necessity for collaborative research endeavors to fully comprehend and effectively combat these viral threats, thereby safeguarding global health and ensuring a resilient response to future outbreaks.